Challenging an appeal in the Code of Shari’a Procedure – A comparative study between Jordanian and Palestinian legislation and the Family Affairs Law – - Abou-Rass, Bayyan Kamal; Ghithan, Yousef Ali (Journal of Economic, Administrative and Legal Sciences, 2022)
This study aimed to explore the challenge of appeal in the Jordanian Sharia and 48 Palestinians law of Sharia Procedure, and the Family Affairs Law. It aimed to explain the similarities and differences between them. To achieve this purpose, the researcher adopted the description analytical approach and the comparative method. The study was divided into three topics: First, the definition of challenge of appeal through jurisprudence and law and its legality. Second, the challenge of appeal in the Jordanian law of Sharia procedure and the courts of civil and Sharia Family Affairs in the Green Line. The results indicated that the Jordanian and the Palestinian Sharia procedure laws are similar in the two kinds of optional and obligatory appeal. The Family Affairs Law, on the other hands, does not imply such legislations, and the civil law does not involve these kinds of appeals. Also, in both the Jordanian and the Palestinian Sharia Procedures laws, the appeal is obligatory regarding Allah’s right. The reason behind this is that is unacceptability of waving Allah’s rights. The family law, in contrast does not include this legislation. On the other hand, the three laws are different concerning the period of the time of the appeal. The Jordanian Sharia Procedure Law decided this period to be (30) days, while the Palestinian (20) days, and the Family Affairs Law identified this period as (60) days. In light of these results, the study recommends to produce a unified Islamic Procedure law in the interior Palestine which has mixture of Palestine legislation Code (1918-1925) and the Ottoman Procedure laws. Therefore, this requires producing a clear and unified law which regulates the Islamic court and the court of family affairs. Thus, each court’s capacities are identified to reform the issue of application priority.